Find the Slope and Y-Intercept (-2,2) , (4,2)

Math
(-2,2) , (4,2)
Find the value of the slope.
Tap for more steps…
Slope is equal to the change in y over the change in x, or rise over run.
m=change in ychange in x
The change in x is equal to the difference in x-coordinates (also called run), and the change in y is equal to the difference in y-coordinates (also called rise).
m=y2-y1x2-x1
Substitute in the values of x and y into the equation to find the slope.
m=2-(2)4-(-2)
Simplify.
Tap for more steps…
Reduce the expression by cancelling the common factors.
Tap for more steps…
Cancel the common factor of 2-(2) and 4-(-2).
Tap for more steps…
Rewrite 2 as -1(-2).
m=-1⋅-2-(2)4-(-2)
Factor -1 out of -1(-2)-(2).
m=-1(-2+2)4-(-2)
Reorder terms.
m=-1(-2+2)4-2⋅-1
Factor 2 out of -1(-2+2).
m=2(-1(-1+1))4-2⋅-1
Cancel the common factors.
Tap for more steps…
Factor 2 out of 4.
m=2(-1(-1+1))2(2)-2⋅-1
Factor 2 out of -2⋅-1.
m=2(-1(-1+1))2(2)+2(1)
Factor 2 out of 2(2)+2(–1).
m=2(-1(-1+1))2(2+1)
Cancel the common factor.
m=2(-1(-1+1))2(2+1)
Rewrite the expression.
m=-1(-1+1)2+1
m=-1(-1+1)2+1
m=-1(-1+1)2+1
Add -1 and 1.
m=-1⋅02+1
m=-1⋅02+1
Simplify the denominator.
Tap for more steps…
Multiply -1 by -1.
m=-1⋅02+1
Add 2 and 1.
m=-1⋅03
m=-1⋅03
Simplify the expression.
Tap for more steps…
Multiply -1 by 0.
m=03
Divide 0 by 3.
m=0
m=0
m=0
m=0
Find the value of the y-intercept.
Tap for more steps…
Substitute the value of m into the slope-intercept form of the equation, y=mx+b.
y=(0)⋅x+b
Substitute the value of x into the slope-intercept form of the equation, y=mx+b.
y=(0)⋅(-2)+b
Substitute the value of y into the slope-intercept form of the equation, y=mx+b.
2=(0)⋅(-2)+b
Rewrite the equation as (0)⋅(-2)+b=2.
(0)⋅(-2)+b=2
Simplify (0)⋅(-2)+b.
Tap for more steps…
Multiply 0 by -2.
0+b=2
Add 0 and b.
b=2
b=2
b=2
The values of the slope and y-intercept are m=0 and b=2.
m=0
b=2
Find the Slope and Y-Intercept (-2,2) , (4,2)

Download our
App from the store

Create a High Performed UI/UX Design from a Silicon Valley.

Scroll to top